"Formulasi dan Evaluasi Sediaan Topikal Nanogel Mengandung Zinc Oxide Nanopartikel Ekstrak Air Kulit Buah Pinang Muda (Areca Catechu L.) dan Aktivitas sebagai Antimikroba" - Apriando Damanik; Vera Estafania Kaban; Astriani Natalia Br. Ginting (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Skin infections caused by Candida albicans require safe and effective natural alternative treatments. This study aims to formulate and evaluate a topical nanogel preparation containing Zinc Oxide Nanoparticles (ZnO-NP) and aqueous extract of young areca nut (Areca catechu L.) with extract concentrations of 2%, 4%, and 6%, using Carbopol 940 as the gel base. Particle size characterization using a Particle Size Analyzer (PSA) yielded results of F0 (40±2 nm), F1 (51±3.46 nm), F2 (46.6±2.88 nm), and F3 (34.6±1.15 nm), all within the nanogel range of 20–200 nm. Antifungal activity testing against Candida albicans using the well diffusion method on PDA medium yielded inhibition zones: 6% concentration (17.22 ± 0.29 mm), 4% (13.47 ± 0.31 mm), 2% (12.58 ± 0.69 mm), positive control ketoconazole (28.62 ± 0.52 mm), and negative control (0 mm). The formulation with a 6% extract concentration (F3) yielded the smallest particle size and the largest inhibition zone, equivalent to 60.17% efficacy compared to ketoconazole. In conclusion, the ZnO-NP-synthesized young areca nut peel extract nanogel has potential as an effective topical antimicrobial formulation with dose-dependent activity.